(untitled) (Journal of Asian Development Studies, 2024)
This research paper explores the obstacles to sustainable development in Pakistan’s higher education institutions (HEIs), focusing on challenges in implementing sustainability initiatives within academic and administrative settings. Despite the global emphasis on sustainability, Pakistani HEIs face several barriers that hinder the integration of sustainable development into curricula, research, and campus operations—the research problem centers around understanding these challenges and their impact on promoting sustainability in higher education. The study aims to identify the key obstacles preventing the effective implementation of sustainable development initiatives in Pakistani HEIs. Theoretical frameworks on sustainable development in education and institutional change guide the research. Phenomenology is a type of qualitative research involving semi-structured interviews with lecturers, professors, and educational administrators from various HEIs across Pakistan. Data is analyzed using thematic analysis to uncover recurring themes related to sustainability challenges. Results of the study revealed that insufficient policy support, inadequate funding, a lack of faculty training, and limited student engagement are significant obstacles to sustainability in HEIs. Additionally, participants emphasized the need for better institutional strategies and more robust government policies. The study underscores the urgent need for policy reforms, capacity-building initiatives, and increased financial support to promote sustainable development in Pakistani HEIs. Recommendations include improving policy alignment with global sustainability goals, fostering public-private partnerships, and integrating sustainability into academic curricula and research practices.